2021
DOI: 10.1017/s2040174421000374
|View full text |Cite
|
Sign up to set email alerts
|

Altered neurodevelopmental DNA methylation status after fetal growth restriction with brain-sparing

Abstract: It is under debate how preferential perfusion of the brain (brain-sparing) in fetal growth restriction (FGR) relates to long-term neurodevelopmental outcome. Epigenetic modification of neurotrophic genes by altered fetal oxygenation may be involved. To explore this theory, we performed a follow-up study of 21 FGR children, in whom we prospectively measured the prenatal cerebroplacental ratio (CPR) with Doppler sonography. At 4 years of age, we tested their neurodevelopmental outcome using the Wechsler Preschoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…It has been confirmed that BDNF is involved in depression-related behavioral phenomena and the therapeutic effect of antidepressants. The higher degree of CpG methylation of the BDNF promoter region is associated with a significant decrease in the synthesis of this factor in neurons [ 38 ]. In addition, it has been confirmed that the methylation levels of the BDNF promoter are elevated in patients with depressive symptoms and those with suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that BDNF is involved in depression-related behavioral phenomena and the therapeutic effect of antidepressants. The higher degree of CpG methylation of the BDNF promoter region is associated with a significant decrease in the synthesis of this factor in neurons [ 38 ]. In addition, it has been confirmed that the methylation levels of the BDNF promoter are elevated in patients with depressive symptoms and those with suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that at 11–13 weeks, intertwin discordance in the crown–rump length can exceed 20%, with a risk of fetal demise of 70% for the small twin 21 . Similarly, low oxygenation, as demonstrated previously in the context of neurodevelopment in singleton pregnancy with fetal growth restriction and brain sparing 22 , could cause epigenetic modification via DNA methylation or expression of microRNAs in early cardiogenesis, thereby altering gene regulation. Epigenetic analysis identified differentially methylated regions in the promoters of genes involved in cardiac development and lateralization in monozygotic twins discordant for CHD 23–25 .…”
Section: Discussionmentioning
confidence: 88%
“…Richter et al observed altered methylations in the neurodevelopmental DNA among fetal growth restricted fetuses that were subject to brain-sparing. 19 Specifically, the authors reported significant hypermethylation at a binding site for cyclic adenosine monophophate response element binding protein (CREB) of BDNF promoter exon 4 and hypomethylation at an HRE located within the neurotrophic tyrosine kinase, receptor, type 2 (NTRK2) promoter.…”
Section: Resultsmentioning
confidence: 99%